SNOWBALL-THROWING METHOD EDUCATION INCREASES THE KNOWLEDGE AND ATTITUDES OF ADOLESCENTS ABOUT THE MATURATION OF MARRIAGE AGE (PUP) - Narmin, Narmin; Amsal, Amsal; Admasari, Yuli; Amalia, Munifa (UNIVERSITAS AIRLANGGA, 2024)
Background: Maturation of Marital Age is an effort to raise the age of child marriage. The number of underage marriages results in rapid population development, high maternal and infant mortality rates, low maternal and child health, families are often not harmonious, domestic violence occurs, and is prone to divorce. The rate of child marriage in Central Sulawesi is very high, one of which is in Donggala district. Donggala Regency ranks 3rd with 196 child marriages in 2022. A contributing factor is the lack of knowledge and attitudes of adolescents about maturing marriage age. The purpose of the study was to determine the effect of snowball throwing method counseling on the management and attitudes of adolescents about the maturation of marriage age at SMKS Al-Amin Wani Method: The pre-experimental research with one group pretest-posttest design was conducted from April 14 to May 20, 2023, at SMKS Al-Amin Wani. Proportional stratified random sampling technique of 75 respondents. Analyzes data through the Wilcoxon test. Result: 31 respondents (41.3%) is 16 years old, 55 respondents (73.3%) is female. the most dominant knowledge was in a good category, 75 respondents (100%). Average increase in knowledge and attitude score of 38.00 and p-value of 0.000. Conclusion: Education on snowball throwing method can improve teenagers' knowledge and attitudes about marriage-age maturity at SMKS Al-Amin Wani.